Determination of the Static Anthropometric Characteristics of Iranian Microscope Users Via Regression Model - Toktam Balandeh; Mohsen razeghi; Zahra Zamanian (Shiraz University of Medical Sciences, 2016)
Background: Anthropometry is a branch of Ergonomics that considers the measurement and description of the human body dimensions. Accordingly, equipment, environments, and workstations should be designed using user-centered design processes. Anthropometric dimensions differ considerably across gender, race, ethnicity and age, taking into account ergonomic and anthropometric principles. The aim of this study was to determine anthropometric characteristics of microscope users and provide a regression model for anthropometric dimensions. Methods: In this cross-sectional study, anthropometric dimensions (18 dimensions) of the microscope users (N=174; 78 males and 96 females) in Shiraz were measured. Instruments included a Studio meter, 2 type calipers, adjustable seats, a 40-cm ruler, a tape measure, and scales. The study data were analyzed using SPSS, version 20. Results: The means of male and female microscope users' age were 31.64±8.86 and 35±10.9 years, respectively and their height were 161.03±6.87cm and 174.81±5.45cm, respectively. The results showed that sitting and standing eye height and sitting horizontal range of accessibility had a significant correlation with stature. Conclusion: The established anthropometric database can be used as a source for designing workstations for working with microscopes in this group of users. The regression analysis showed that three dimensions, i.e. standing eye height, sitting eye height, and horizontal range of accessibility sitting had a significant correlation with stature. Therefore, given one's stature, these dimensions can be obtained with less measurement.